PENINGKATAN KINERJA CONTROL VALVE AKIBAT FENOMENA RESET WINDUP PADA SISTEM REBOILER - Megarini Hersaputri; Yuniarto Yuniarto; Ari Bawono Putranto; Dista Yoel Tadeus; Fakhruddin Mangkusasmito (BERKALA FISIKA, 2022)
One of the important elements of the LPG production process is the control valve. Control valves is almost 90% found in the LPG process. The size of the control valve must have a standard size so that the performance of the control valve is more optimal. Control valve CV1 is a control valve to regulate the flow of steam to reboiler in the distillation column. CV1 at the gas processing plant which is the object of research is experiencing the phenomenon of reset wind up, reset wind up is a  phenomenon  where  the  variable  control  valve  process  is  unable  to  reach  the  set  point  at  the indicating point (TIC) even though the control valve has reached 100% opening. The phenomenon of reset wind up on CV1 affects the temperature  of the steam used for the reboiler. If the steam produced  by  the  reboiler  is  not  up  to  separation  standard  in  propane  distillation,  then  the  C3 separation is not perfect and will affect the LPG yield. To improve the performance of the control valve, it is necessary to calculate the coefficient valve on the control valve and replace the internal valve parts. From this research, the coefficient value is 591, control valve body type ET-667 with diameter of 8 "and a travel indicator 2" is 567. This difference also occurs when the valve openings are 50%, 72%, 75% and 100%. The calculated coefficient valve value should be less than the data sheet. Internal part replacement was also carried out in this study, by replacing the cage on the control valve into a cage with a linear type.